2016
DOI: 10.1186/s12884-016-0953-5
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral artery dissection in hypertensive disorders of pregnancy: a case series and literature review

Abstract: BackgroundArterial dissection is a rare complication of pregnancy and puerperium. There have been reports of aortic, coronary and cervical artery dissection in association with preeclampsia, however, vertebral artery dissection is rarely reported particularly in the antenatal setting in the presence of a Hypertensive Disorder of Pregnancy (HDP).The general annual incidence of symptomatic spontaneous cervicocephalic arterial dissection is 0.0026 % and a data registry reported that 2.4 % of these occurred in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…Events most commonly occur in the postpartum period with an estimated annual incidence of 2.6–3 per 100,000 pregnancy hospitalizations [ 4 ]. VAD has been associated with HDP [ 2 , 5 ]. Leffert et al performed a national cross-sectional study of over 81 million pregnancy hospitalizations and demonstrated that women with HDP were 5.2 times more likely to have a stroke than those without HDP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Events most commonly occur in the postpartum period with an estimated annual incidence of 2.6–3 per 100,000 pregnancy hospitalizations [ 4 ]. VAD has been associated with HDP [ 2 , 5 ]. Leffert et al performed a national cross-sectional study of over 81 million pregnancy hospitalizations and demonstrated that women with HDP were 5.2 times more likely to have a stroke than those without HDP.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertensive disorders of pregnancy (HDP) are associated with vascular events, including stroke (Liffert et al) and cervical artery dissection [ 1 ]. However, vertebral artery dissection (VAD) is rare [ 2 , 3 ]. We describe a 31-year-old woman with a history of preeclampsia who presented 10 days postpartum with an ischemic posterior cerebellar stroke secondary to VAD.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial dissection is a rare complication of pregnancy and puerperium. There have been reports of cervical carotid, vertebral and intracranial artery dissection in association with preeclampsia [ 46 ]. Headache is the most frequent inaugural symptom, described as severe, unilateral (ipsilateral to the dissected vessel), with a sudden (even thunderclap) onset.…”
Section: Clinical Headache Phenotypes and Observational Studies In Prmentioning
confidence: 99%
“…Outside of pregnancy, cervical artery dissections are usually treated with either a vitamin K antagonist or antiplatelet (acetylsalicylic acid) for 3-6 months. Case reports of women treated for carotid and vertebral dissections occurring in both the antenatal and early post-partum period indicate the same management strategies are used [57][58][59][60] without reported adverse effects for the mother or infant. Both aspirin and warfarin were used for secondary prevention among 68 women who had suffered a previous CVST prior to pregnancy.…”
Section: D Pre-existing Diabetes and Gestational Diabetes For Strokmentioning
confidence: 99%